Ketentuan Umum Perpajakan (KUP) dan Tatacara Perpajakan - Indah Amelia; Aprilia Regitasya Parinduri; Habima Perdana Kusuma; Dini Vientiany (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
The General Provisions and Tax Procedures (KUP) constitute the legal basis of the Indonesian tax system, governing the rights and obligations of taxpayers and tax administration procedures. This study aims to understand the definition, function, purpose, and implementation of the tax system in Indonesia. The research method used is a literature study, utilizing journals, books, and the latest tax regulations as data sources. The results indicate that the KUP plays a crucial role in creating an orderly and effective tax system that provides legal certainty for both the public and the government. Modernizing tax administration through digital systems also helps improve taxpayer compliance in Indonesia.